International trade and the transmission of temperature shocks - Daniel Osberghaus; Oliver Schenker (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
We examine how the adverse impacts of weather shocks are distributed through the trade network. Exploiting a rich, theoretically derived, fixed effects structure, we find significant negative short-run effects of high temperature on exports. A month with an average temperature above 30 êC implies export losses of around three percent. These effects are increasing in the labour-intensity of exports. Using our structural Gravity model, we assess the general equilibrium incidence of these temperature shocks. We find that equilibrium adjustments reduce the economic costs by around 20 percent, but significant costs arise also for countries not directly exposed to high temperatures.
Keywords: F14; F18; Q54; 330; International trade; Temperature; Extreme weather; Structural Gravity